Report on currency and finance 1990-91 : vol I : economic review - Reserve Bank of India ([Bombay] : Reserve Bank of India, 1991)
This volume contains information on the statistical analysis on currency and finance for the year (April 1990 to March1991)
Issues also carry theme title and appears in volumes
usc 10/04/2019
Ref.
Keywords: Banks and banking, Central; Currency question; Finance; Public finance; Ecoonomic conditions; India